2021
DOI: 10.2196/27183
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ Likelihood to Engage With Information and Misinformation on Twitter About the Relative Harms of e-Cigarette Use: Results From a Randomized Controlled Trial

Abstract: Background Information and misinformation on the internet about e-cigarette harms may increase smokers’ misperceptions of e-cigarettes. There is limited research on smokers’ engagement with information and misinformation about e-cigarettes on social media. Objective This study assessed smokers’ likelihood to engage with—defined as replying, retweeting, liking, and sharing—tweets that contain information and misinformation and uncertainty about the harms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“… 14 Participants were also more likely to engage with (e.g. share, like) tweets that e-cigarettes were just as or more harmful than smoking, 15 we also found that affective responses and perceived relative harm following exposure to misinformation about e-cigarette harms may mediate the relationship with intention to purchase e-cigarettes. 16 …”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“… 14 Participants were also more likely to engage with (e.g. share, like) tweets that e-cigarettes were just as or more harmful than smoking, 15 we also found that affective responses and perceived relative harm following exposure to misinformation about e-cigarette harms may mediate the relationship with intention to purchase e-cigarettes. 16 …”
Section: Introductionsupporting
confidence: 58%
“…14 Participants were also more likely to engage with (e.g. share, like) tweets that e-cigarettes were just as or more harmful than smoking, 15 we also found that affective responses and perceived relative harm following exposure to misinformation about e-cigarette harms may mediate the relationship with intention to purchase e-cigarettes. 16 This current study examined the effect of brief exposure to misinformation found on Twitter about e-cigarette harms on smoker's knowledge and harm perceptions of e-cigarettes relative to combustible cigarettes, across US versus UK populations.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, engaging with e-cigarette content on social media can promote discussions about the health effects of using e-cigarettes among young people; thus, engagement with social media is an important activity to measure. From the limited research base examining engagement and e-cigarette social media messaging, research has found that young people shared memes when they were funny [2], and individuals engaged more with posts comparing e-cigarettes with cigarettes [17]. Other research examining e-cigarette industry sponsored posts and social media messaging have predominately focused on analyzing the content of posts [18,19] or characteristics of posts (e.g., likes, shares) [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results demonstrate that social media content can be used for overall infoveillance, and such data could inform future, individual-level detection models to identify at-risk posts and users. A systematic review conducted by Kwon and Park [ 32 ] found that sentiment regarding vaping tended to be more positive across social media sites, and previous research on Twitter has demonstrated that those who smoke are more likely to engage with misinformation about vaping [ 43 ]. Studies conducted on Reddit posts have illustrated health symptoms associated with vaping [ 44 ] and highlighted communities aimed to support those wanting to quit vaping [ 45 ].…”
Section: Introductionmentioning
confidence: 99%